Peran kepemilikan manajerial dalam memoderasi pengaruh Profitabilitas Leverage dan Ukuran Perusahaan Terhadap Manajemen Laba - Wardana, Defa Nanda; Kusbandiyah, Ani; Hariyanto, Eko; Amir, Amir (Owner : Riset dan Jurnal Akuntansi, 2024)
This study is intended to measure the effect of profitability, leverage, and company size impact profit management with managerial ownership in the role of a moderating variable. This study is categorized as quantitative research. The study’s target population on within the sector of mining, which were listed on the Indonesia Stock Exchange from 2019 to 2021. Employing purposive sampling, a sample comprising 30 companies that closely adhered to the criteria was selected, resulting in a dataset of 90 observations. The study relies on secondary data, specifically financial statements from mining sector firms listed on The IDX (Indonesian Stock Exchange), accesible via www.idx.co.id. The analysis of data was conducted through panel data regression analysis, and the processing task involved the utilization of Eviews software. The results revealed that earnings management is positively associated with profitability and negative associated with firm size, earnings management is not affected by leverage. And managerial ownership does not possess the capacity to moderate the relationship between profitability, leverage, and firm size with earnings management.